TELAAH KRITIS IMPLEMENTASI PP 46/2013 TERHADAP UU N0. 36/2008 PADA SEKTOR UMKM - Probowulan, Diyah (Universitas Muhammadiyah Jember, 2016)
The Government through the Directorate General of Taxation issued a policy in 2013 in the form of Government Regulation (PP) Number 46 of 2013 regarding the application of a flat rate of 1% on any business that has a maximum income of Rp. 4.8 billion. Application of PP 46 in 2013 will inevitably have to be done by all trained partners or SMEs in Indonesia, which has a turnover of under Rp. 4.8 billion. In the period of the commencement of the year 2013 until today of course there are various phenomena in the field. Therefore, this study aimed to describe the behavior of the partners in addressing the implementation of PP 46 in 2013. This study used a qualitative approach with intrepetif perspective. The qualitative approach is research done in certain settings that exist in real life (naturally) with the intent to investigate and understand the phenomenon: what happened, why it happened and how it happened ?. The main objective of qualitative research is to make a fact easily understood (understandable) and that allows (by model) can generate new hypotheses. Based on pre-defined criteria, this study used the key person in approaching research informants. While the mention of the name of the informant, the author uses a pseudonym, which means that the author will not use the real names of informants, but pseudonyms or initials.Keywords: Government Regulation (PP) Number 46 of 2013, intrepetif perspective.